Characteristics of micro-amplitude structure at fault edge and its effect on residual oil distribution: a case study from the Northern Xingshugang development area, Songliao Basin, China. (3rd May 2019) - Wang, Haixue; Sun, Yonghe; Cheng, Zhiyuan; Fu, Xiaofei; Shen, Zhongshan; Li, Xin
Abstract: A quantitative predictive method was established by utilizing fault throw–distance curve, average throw gradient, and structural amplitude variation gradient, combined with data of water cut and daily oil productive levels. The results indicate that micro-amplitude structures at fault edge are controlled by fault segments growth mechanism, and positive micro-amplitude structures correspond to location between fault segment growth points in the footwall. The amplitudes mainly depend on the average throw gradient at the maximum throw of corresponding structural segments, and the larger the throw is, the higher the micro-amplitude. The micro-amplitude structures are preferential regions to increase oil fields productivity. The quantitative prediction for micro-amplitude structures provides a set of rapid and effective methods for residual oil exploration at fault edge.